Employment, inequality and the UK national minimum wage over the medium-term - Peter Dolton; Chiara Rosazza-Bondibene; Jonathan Wadsworth (Institute for the Study of Labor (IZA), 2010)
This paper assesses the impact of the National Minimum Wage (NMW) on employment and inequality in the UK over the decade since its introduction in 1999. Identification is facilitated by using variation in the bite of the NMW across local labour markets and the different sized year on year up ratings of the NMW. We use an 'incremental differences-in-differences' (IDiD) estimator which allows us to estimate the effects of the NMW in each year since its introduction. We find that an increased bite of the NMW is associated with falls in lower tail wage inequality. Moreover, while the average employment effect of the NMW over the entire period is broadly neutral, there are small but significant positive employment estimates from 2003 onward, when the average bite of the NMW was at its highest since its introduction.
Keywords: J0; J2; J3; 330; minimum wage; employment; inequality